2022
DOI: 10.7602/jmis.2022.25.3.112
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative assessment of parathyroid perfusion using indocyanine green angiography in robotic thyroidectomy

Abstract: In recent da Vinci robot systems (Intuitive Surgical), near-infrared f luorescence imaging (Firef ly technology) has been used. With this technique, it is possible for surgeons to see important structures well beyond the limits of their eyes; hence, surgeons can safely operate and make critical decisions accurately using image-guided surgery. Because parathyroid glands (PTGs) are small and embedded in the surrounding tissues, such as lymph nodes and fat, it is often very hard for surgeons to identify PTGs. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…One of the strengths of this study is its emphasis on the use of ICG for the easy detection and successful removal of diseased parathyroid glands, whereas many previous studies primarily focused on the use of ICG for preserving parathyroid glands in thyroid surgery [ 11 , 12 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. To our knowledge, we have reported in this study the largest number of cases of robot BABA parathyroidectomy using ICG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the strengths of this study is its emphasis on the use of ICG for the easy detection and successful removal of diseased parathyroid glands, whereas many previous studies primarily focused on the use of ICG for preserving parathyroid glands in thyroid surgery [ 11 , 12 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. To our knowledge, we have reported in this study the largest number of cases of robot BABA parathyroidectomy using ICG.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of near-infrared (NIR) fluorescence imaging in da-Vinci robot systems (Intuitive Surgical Inc., Sunnyvale, CA, USA), known as Firefly TM technology (Novadaq Technologies Inc., Mississauga, ON, Canada), was proposed for the identification of parathyroid glands during thyroidectomy to preserve the parathyroid glands [ 10 ]. While previous studies mainly utilized ICG as a strategy to preserve parathyroid glands during thyroidectomy, we suggest that pathologic parathyroid glands also be identified via ICG fluorescence under the Firefly TM function in robot surgery [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study [ 5 ], the authors assessed the perfusion of the parathyroid glands using indocyanine green angiography in transoral robotic thyroidectomy. They have presented a video clip of transoral robotic total thyroidectomy, which shows the three typical statuses of the parathyroid glands after thyroid surgery (well-perfused, poorly or non-perfused, and congested) and explains how to deal with each status of the parathyroid glands.…”
mentioning
confidence: 99%
“…They have presented a video clip of transoral robotic total thyroidectomy, which shows the three typical statuses of the parathyroid glands after thyroid surgery (well-perfused, poorly or non-perfused, and congested) and explains how to deal with each status of the parathyroid glands. They have shown that intraoperative indocyanine green angiography has the potential to lower the risk of permanent hypoparathyroidism after thyroid surgery by supporting auto-transplantation of devascularized parathyroid glands detected by the technique [ 5 ].…”
mentioning
confidence: 99%